Linear Programming on Portfolio Optimization: Empirical Evidence from BIST Mining Industry Index (Global Journal of Management and Business Research, 2016)
A lot of methods are improved for the portfolio optimization within classical approach. Quadratic programming, one of these methods, has many disadvantages, so alternative methods are studied to improve. MAD Method, an improved new method, is converted portfolio optimization problem into a linear programming problem. MAD Method is demonstrated and a case study is done by using stock certificate which belongs to BIST Mining Sector.
Keywords: BIST mining sector; linear programming; portfolio optimization